2019
DOI: 10.1016/j.fertnstert.2019.08.009
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of body mass index on pregnancy outcomes with the freeze-all strategy in women with polycystic ovarian syndrome

Abstract: Objective: To investigate the effects of body mass index (BMI) on assisted reproductive outcomes with the freeze-all strategy for patients with polycystic ovary syndrome (PCOS). Design: Retrospective cohort study. Setting: Tertiary care academic medical center. Patient(s): A total of 3,079 women with PCOS across different BMIs at our institution from January 2015 to May 2017 were stratified into cohorts. Intervention(s): None. Main Outcome Measure(s): Implantation rate, clinical pregnancy rate, early miscarria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 29 publications
(34 reference statements)
5
52
1
Order By: Relevance
“…Outcomes of interest were reported in 11182 patients in 17 retrospective cohort studies ( 20 26 , 28 , 30 – 36 , 40 , 41 ), three prospective cohort studies ( 38 , 39 , 42 ) and two case-control studies ( 27 , 37 ). Fourteen studies were conducted in China ( 22 , 23 , 25 , 28 , 30 – 33 , 35 , 36 , 38 , 39 , 41 , 42 ), five in the USA ( 20 , 21 , 24 , 26 , 27 ), and the remaining three in Japan ( 37 ), Turkey ( 34 ), and Australia ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Outcomes of interest were reported in 11182 patients in 17 retrospective cohort studies ( 20 26 , 28 , 30 – 36 , 40 , 41 ), three prospective cohort studies ( 38 , 39 , 42 ) and two case-control studies ( 27 , 37 ). Fourteen studies were conducted in China ( 22 , 23 , 25 , 28 , 30 – 33 , 35 , 36 , 38 , 39 , 41 , 42 ), five in the USA ( 20 , 21 , 24 , 26 , 27 ), and the remaining three in Japan ( 37 ), Turkey ( 34 ), and Australia ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes of interest were reported in 11182 patients in 17 retrospective cohort studies ( 20 26 , 28 , 30 – 36 , 40 , 41 ), three prospective cohort studies ( 38 , 39 , 42 ) and two case-control studies ( 27 , 37 ). Fourteen studies were conducted in China ( 22 , 23 , 25 , 28 , 30 – 33 , 35 , 36 , 38 , 39 , 41 , 42 ), five in the USA ( 20 , 21 , 24 , 26 , 27 ), and the remaining three in Japan ( 37 ), Turkey ( 34 ), and Australia ( 40 ). Seventeen studies measured BMI ( 20 26 , 30 – 32 , 34 38 , 41 , 42 ), four assessed age ( 28 , 30 , 37 , 40 ), three evaluated insulin resistance ( 30 , 37 , 42 ), five investigated chromosome aberrations ( 26 , 30 , 31 , 33 , 39 ), and the other four assessed hyperandrogenism ( 27 , 30 , 37 , 42 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of clinical studies indicate that impaired endometrial function leads to recurrent miscarriages, preterm births, endometrial hyperplasia, and canceration in patients with PCOS [23]. Other studies have shown an association between many endometrial cell lines and inflammation-related molecular disorders under PCOS conditions [24].…”
Section: Introductionmentioning
confidence: 99%